Cytotoxicity, antimutagenicity and molecular docking of benzimidazole derivatives as anticancer agents - Azahar, Nurul Hafizan (2021)
Benzimidazole, a fused heterocyclic compound comprising benzene and imidazole rings, is a well-known moiety that has garnered considerable interest in medicinal chemistry due to its wide range of pharmacological activity in a variety of disease models, including cancer. Due to its broad spectrum of therapeutic potential, many modifications and optimizations have been made to its backbone, resulting in the production of many of its derivatives. The purpose of this study was to assess the cytotoxicity, mutagenicity, and antimutagenicity of four benzimidazole derivatives: (E)-4-(5,6-dimethyl-1H-benzo[d]imidazol-2- yl)-N’-(3-hydroxybenzylidene) benzohydrazide (1), (E)-N’-(2,5- dihydroxybenzylidene)-4-(5,6-dimethyl-1H-benzo[d]imidazol-2-yl) benzohydrazide (2), (E)-N’-(2,4-dihydroxybenzylidene)-4-(5,6-dimethyl-1Hbenzo[ d]imidazol-2-yl) benzohydrazide (3), and (E)-4-(5,6-dimethyl-1Hbenzo[ d]imidazol-2-yl)-N’-(2-hydroxybenzylidene) benzohydrazide (4). To our knowledge, these benzimidazole derivatives have not been explored for the stated activities. The potential molecular interactions of these compounds with the target proteins Bcl-2, Bcl-xL, and mutant p53-R273H were also investigated. The MTT assay was conducted to determine the cytotoxic effects of benzimidazole derivatives (1 – 4) on HeLa, HT-29, and MDA-MB-231 cancer cell lines. Following that, the Ames test was performed to evaluate the mutagenic and antimutagenic potential of the compounds. Then, the structure-activity relationship (SAR) of benzimidazole derivatives was analyzed based on the results obtained. Further, molecular docking was employed to predict the possible interactions of the selected benzimidazole derivatives with the Bcl-2, Bcl-xL, and mutant p53-R273H proteins. Except for compound 2, all benzimidazole derivatives demonstrated varying degrees of cytotoxicity against the tested cancer cells. When compared to 5-fluorouracil (5-FU), compound 4 showed the most promising cytotoxicity with lower IC50 values against HeLa (48 h: 9.86 ± 1.50 μM), HT-29 (48 h: 4.66 ± 0.16 μM) and MDA-MB-231 (24 h: 7.80 ± 0.19 μM; 48 h: 8.83 ± 0.64 μM) cells. Compound 3 also presented high cytotoxicity compared to 5-FU, with IC50 values of 8.89 ± 2.62 μM (48 h) in HT-29 and 10.88 ± 1.39 μM (24 h) and 10.10 ± 2.90 μM (48 h) in MDA-MB-231 cells. Likewise, compound 1 had lower IC50 values in HeLa (48 h: 9.09 ± 0.46 μM) and HT-29 (48 h: 13.47 ± 3.50 μM) cells, in comparison to 5-FU. The mutagenicity assessment showed all benzimidazole derivatives were not mutagenic against the TA98 and TA100 strains in the absence of metabolic activation. In the presence of metabolic activation, it was observed that compound 1 induced a frameshift mutation in the TA98 strain, whereas other compounds were not mutagenic in both tester strains. Additionally, all derivatives showed significant antimutagenicity in both tester strains. The SAR analysis proposed that the ortho-OH substitution on the phenyl ring has a substantial influence on the cytotoxicity, mutagenicity, and antimutagenicity of benzimidazole derivatives. The molecular docking analysis demonstrated a high-affinity binding of compound 3 to the Bcl-2 protein and compounds 3 and 4 to the mutant p53-R273H protein relative to the reference standards. The results suggested that compound 3 may act as a ligand inhibitor for Bcl-2 and that compounds 3 and 4 may act as ligand activators for the mutant p53-R273H.